Effect of Divalent Cations (Cu, Zn, Pb, Cd, and Sr) on Microbially Induced Calcium Carbonate Precipitation and Mineralogical Properties - Kim, Yumi; Kwon, Sunki; Roh, Yul (Frontiers in Microbiology, 2021)
Microbially induced calcium carbonate precipitation (MICP) is a bio-geochemical process involving calcium carbonate precipitation and possible co-precipitation of other metals. The study investigated the extent to which a urease-positive bacterium, Sporosarcina pasteurii, can tolerate a range of metals (e.g., Cu, Zn, Pb, Cd, and Sr), and analyzed the role of calcium carbonate bioprecipitation in eliminating these divalent toxicants from aqueous solutions. The experiments using S. pasteurii were performed aerobically in growth media including urea, CaCl2 (30 mM) and different metals such Cu, Zn, Pb and Cd (0.01 ~ 1 mM), and Sr (1 ~ 30 mM). Microbial growth and urea degradation led to an increase in pH and OD600, facilitating the precipitation of calcium carbonate. The metal types and concentrations contributed to the mineralogy of various calcium carbonates precipitated and differences in metal removal rates. Pb and Sr showed more than 99% removal efficiency, whereas Cu, Zn, and Cd showed a low removal efficiency of 30~60% at a low concentration of 0.05 mM or less. Thus the removal efficiency of metal ions during MICP varied with the types and concentrations of divalent cations. The MICP in the presence of divalent metals also affected the mineralogical properties such as carbonate mineralogy, shape, and crystallinity.